Surprising Similarities in Cognitive Footprint of Scientism and Irrational Beliefs - Lukić, Petar; Žeželj, Iris (Studia Psychologica, 2025)
Scientism is a belief that science is superior to any other human endeavor, capable of solving all human problems and that scientists are always knowledgeable and ethical. As this view is extreme and somewhat dogmatic, we tested whether it draws from the same information processing style as beliefs traditionally deemed irrational. This is especially interesting since scientistic and irrational beliefs are incompatible content-wise and thus negatively related. In Study 1 (N = 1003, representative for Serbia) scientistic beliefs were more frequent than anti-scientific beliefs and, expectedly, correlated negatively with conspiracist, paranormal, and pseudoscientific beliefs. Study 2 (online community sample; 186 scientists, 147 laypeople) showed that uncritical trust in science positively correlated to need for closure and uncertainty intolerance, while uncritical trust in scientists negatively correlated with cognitive reflection and cognitive abilities. This indeed indicates a superficial informational processing style typically observed in people prone to irrational beliefs. All reported relationships, however, need to be independently replicated. This apparent paradox illustrates that science could be used as a heuristic, and it highlights the need to cultivate a more realistic view of the science process through formal education and media.